Penyelesaian Kasus Kecelakaan Lalu Lintas pada Polresta Pulau Ambon dan P.P. Lease: Penelitian - Ali Muhajirin; Fatimah Sialana; A.M.D. Ratuanak (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Traffic accidents are events that occur on public roads unintentionally and unexpectedly, resulting in losses, both material and fatalities. This study uses a qualitative research method with a qualitative descriptive approach to reveal facts or phenomena that occur according to the reality in the field. The results of this study indicate that the main factors causing traffic accidents are alcoholic beverages, damaged road conditions and human negligence which cause accidents. Human negligence factors such as not wearing helmets and obeying traffic rules are things that are violated in traffic rules so that they can cause accidents and fatalities. Damaged road conditions that are not immediately repaired, plus the lack of warning signs, can trigger accidents, especially for drivers who drive fast or are not alert, with a higher risk for motorcyclists. Prevention efforts that have been made by the Ambon Island Police & P.P. Lease includes socialization, safety operations, and law enforcement for those who violate traffic rules and patrols at accident-prone points aimed at reducing the number of accidents. Although there have been improvements, the effectiveness of these efforts still needs to be improved through the use of technology, increased education, and cooperation with related agencies and the community to create safer traffic.